2002
DOI: 10.1590/s0100-879x2002000800018
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery after exercise: relations to heart rate variability and complexity

Abstract: Physical exercise is associated with parasympathetic withdrawal and increased sympathetic activity resulting in heart rate increase. The rate of post-exercise cardiodeceleration is used as an index of cardiac vagal reactivation. Analysis of heart rate variability (HRV) and complexity can provide useful information about autonomic control of the cardiovascular system. The aim of the present study was to ascertain the association between heart rate decrease after exercise and HRV parameters. Heart rate was monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
198
9
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(257 citation statements)
references
References 27 publications
35
198
9
15
Order By: Relevance
“…The current results show an elevated HR during the first 45 min of recovery compared with pre-exercise rest values, which is consistent with previous data, [36][37][38] but in contrast to Perini et al 18 With regard to the spectral components of HRV, we observed that the relative LF component in the recovery period was not different from pre-exercise rest values, [37][38][39] whereas the HF component during the recovery period was slightly lower than control. 37,38 We have not assessed HRV during exercise, but in an earlier study 40 in which we measured HRV during submaximal exercise (up to 40% of maximal workload), we found a slight increase of the relative LF component from 34 to 41%, and a pronounced decrease in the relative HF component from 32 to 9%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current results show an elevated HR during the first 45 min of recovery compared with pre-exercise rest values, which is consistent with previous data, [36][37][38] but in contrast to Perini et al 18 With regard to the spectral components of HRV, we observed that the relative LF component in the recovery period was not different from pre-exercise rest values, [37][38][39] whereas the HF component during the recovery period was slightly lower than control. 37,38 We have not assessed HRV during exercise, but in an earlier study 40 in which we measured HRV during submaximal exercise (up to 40% of maximal workload), we found a slight increase of the relative LF component from 34 to 41%, and a pronounced decrease in the relative HF component from 32 to 9%.…”
Section: Discussionsupporting
confidence: 92%
“…The slightly reduced HF component recorded post-exercise in comparison with the pre-exercise stage may indicate that parasympathetic withdrawal contributes to autonomic control of the post-exercise tachycardia. 37,39 However, it is likely that other phenomena played a more important role, such as the higher body temperature and stimulation of circulating catecholamines. 41,42 Cross-sectional data showed that endurancetrained participants exhibit a more rapid HR recovery than their untrained counterparts after exercise at similar relative work loads.…”
Section: Discussionmentioning
confidence: 99%
“…They studied the effects of high-intensity sprint exercises on immediate 10 min HRV recovery of trained athletes, and found highly impaired vagal reactivation during the first minutes of recovery. According to previous studies (Hautala et al 2001;Javorka et al 2002;Oida et al 1997;Seiler et al 2007;Takahashi et al 2000), HRV increases slowly towards resting values during recovery after single exercise session, but the effects of endurance exercise may last from minutes (Gladwell et al 2010;Seiler et al 2007) to even 48 hours (Mourot et al 2004), depending on physical TL, i.e. the combined effect of exercise intensity and duration, of the exercise as well as the training status of the subjects.…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 88%
“…Pre-exercise HRV at rest has not been found to explain HR recovery after exercise (Javorka et al 2002), but high modulation of cardiac vagal tone after exercise was associated with high baseline cardiac vagal tone and good aerobic fitness (Tulppo et al 2011). In addition, modulation of cardiac vagal tone was found to be augmented in subjects who had higher peripheral sympathetic outflow in the recovery phase after exercise (Tulppo et al 2011).…”
Section: Heart Rate and Hrv During Recovery After Exercisementioning
confidence: 99%
“…This enhances its utility in detecting subtle changes in the brain state that can find wider scope for applications in electroencephalogram based brain studies. Further studies showed applications of SampEn for heart rate recovery after exercise [Javorka et al, 2002], for heart rate dynamics in schizophrenic subjects [Kim et al, 2004] as well as the quantification of neonatal heart rate before the clinical diagnosis of sepsis [Cao et al, 2004]. Occasionally, traditional complexity measure have yielded contradictory findings when applied to real-world datasets obtained in health and disease states.…”
Section: Further Applicationsmentioning
confidence: 99%